A component of the Sec61 ER protein transporting pore is required for plant susceptibility to powdery mildew - Zhang, Wen-Jing; Hanisch, Susanne; Kwaaitaal, Mark; Pedersen, Carsten; Thordal-Christensen, Hans (Frontiers in Plant Science, 2013)
Biotrophic pathogens, like the powdery mildew fungi, require living plant cells for their growth and reproduction. During infection, a specialized structure called the haustorium is formed by the fungus. The haustorium is surrounded by a plant cell-derived extrahaustorial membrane (EHM). Over the EHM, the fungus obtains nutrients from and secretes effectors into the plant cell. In the plant cell these effectors interfere with cellular processes such as pathogen defense and membrane trafficking. However, the mechanisms behind effector delivery are largely unknown. This paper provides a model for and new insights into a putative transfer mechanism of effectors into the plant cell. We show that silencing of the barley Sec61βa protein results in decreased susceptibility to the powdery mildew fungus. HvSec61βa is a component of both the endoplasmic reticulum (ER) translocon and retrotranslocon pores, the latter being part of the ER-associated protein degradation machinery (ERAD). We provide support for a model suggesting that the retrotranslocon function of HvSec61βa is required for successful powdery mildew fungal infection. HvSec61βa-GFP and a luminal ER marker were co-localized to the ER, which was found to be in close proximity to the EHM around the haustorial body, but not the haustorial fingers. This differential EHM proximity suggests that the ER, including HvSec61βa, may be actively recruited by the haustorium, potentially to provide efficient effector transfer to the cytosol. Effector transport across this EHM-ER interface may occur by a vesicle-mediated process, while the Sec61 retrotranslocon pore potentially provides an escape route for these proteins to reach the cytosol.